Recipes for vitamin A-rich bananas: developed for South Kivu, Democratic Republic of Congo - Nabuuma, Deborah; Kamira, Muller; Simbare, Alice; Ekesa, Beatrice (2020)
Recipes were developed through a participatory process with banana farmers in South Kivu, DRC to incorporate the Vitamin A-rich bananas and improve the nutrient quality of the meals. Recipes are applicable among banana producing and consuming regions of Eastern Africa. The Vitamin A-rich bananas mentioned in these recipes are naturally rich in vitamin A and they are from the countries in the table.